THE ANALYSIS OF SERVICE SATISFACTION LEVEL IN THE IMPLEMENTATION OF TEACHER PROFESSIONAL EDUCATION PROGRAM IN 2020 - Kafrawi, Fatkur Rohman; Sodiq, Syamsul; Julianto, Julianto (Universitas Nahdatul Ulama Surabaya, 2021)
Abstract: The purpose of this research is to identify and to obtain various information related to the level of service satisfaction in the implementation of Teacher Professional Program in 2020. The type of research used is descriptive research. The population in this study were all Teacher Professional Education Program participants in stages 1-4, totaling 1632 students consisting of 15 study programs at the State University of Surabaya. The sample used in this study was 971 students of the Teacher Professional Education Program of 2020 academic year. The data collection method used was a questionnaire. The questionnaire developed by the researchers has 6 indicators including: (1) LMS (Learning Management System), (2) Helpdesk Teacher Professional Education Program IT team, (3) Teacher Professional Education Program Instructors (Lecturers), (4) In-service teachers, (5) Participants, and (6) Material. The data obtained were analyzed descriptively, qualitatively and quantitatively. Based on the results and discussion, it can be concluded that the level of service satisfaction in the implementation of Teacher Professional Education Program in 2020 is good. In addition, it is also supported by the results of the six indicators showing the satisfaction of students who take Teacher Professional Education Program in position 2020 which was held online. Although in general it runs smoothly in the implementation of Teacher Professional Education Program in Position in 2020, however there were still some shortcomings or obstacles that arise in the implementation, especially interactions in the LMS both with instructors, tutors, helpdesk and the learning management system itself. Keywords: Teacher Professional Education Program, Certification, LMS, Descriptive Study. Abstrak: Tujuan penelitian ini adalah untuk mengidentifikasi dan mendapatkan berbagai informasi terkait tingkat kepuasan pelayanan dalam pelaksanaan PPG Dalam Jabatan tahun 2020. Jenis penelitian yang digunakan adalah penelitian deskriptif. Adapun populasi dalam penelitian ini yaitu seluruh peserta PPG Dalam Jabatan tahap 1-4 yang berjumlah 1632 mahasiswa terdiri 15 Prodi yang ada di Universitas Negeri Surabaya. Sampel yang digunakan dalam penelitian ini sebanyak 971 mahasiswa yang mengikuti PPG Daljab tahun 2020. Metode pengumpulan data yang digunakan yakni angket. Angket yang dikembangkan oleh peneliti memiliki 6 indikator diantaranya: (1) LMS, (2) Helpdesk tim IT PPG, (3) Instruktur PPG (Dosen), (4) Guru Pamong, (5) Peserta, dan (6) Materi. Data yang diperoleh akan dianalisis secara deskriptif kualitatif dan kuantitatif. Berdasarkan hasil dan pembahasan dapat disimpulkan tingkat kepuasan pelayanan dalam pelaksanaan PPG Dalam Jabatan tahun 2020 baik. Selain itu juga, didukung hasil dari keenam indikator menunjukkan kepuasan dari mahasiswa yang mengikuti PPG Dalam Jabatan tahun 2020 yang dilaksanakan secara daring. Walaupun secara garis besar berjalan dengan lancar dalam pelaksanaan PPG Dalam Jabatan tahun 2020, tentunya masih ada beberapa kekurangan atau hambatan yang muncul dalam pelaksanaan terutama interaksi dalam LMS baik dengan instruktur, guru pamong, helpdesk dan system lms itu sendiri. Kata Kunci: PPG Dalam Jabatan, Sertifikasi, LMS, Studi Deskriptif.